MAP OF STUDY OF THE QURAN IN THE POSTGRADUATE PROGRAM OF UIN JAKARTA AND UIN YOGYAKARTA PERIOD OF 2005-2012 - Lilik Ummi Kaltsum; Eva Nugraha; Jauhar Azizy (Peminat Ilmu Ushuluddin, 2021)
This article is the result of a study that discusses the map of the study of Quran, which is represented by dissertations written by the Postgraduate programs of UIN Syarif Hidayatullah Jakarta and UIN Sunan Kalijaga Yogyakarta for the period of 2005-2012. This article shows the disproportionate phenomenon between the number of dissertations written in the study of Quran and the quality of the results. It is proven from the slow development of the study of Quran. Qualitatively, there has been no significant development, both in the title and content of the dissertation. It is found that many titles and objects of study are similar between one UIN (State Islamic University) and another UIN or IAIN (State Islamic College). The majority of dissertations still discuss Islamic and humanitarian issues in general, but do not relate them to Indonesian problems. This article uses discourse content analysis.